2003
DOI: 10.1152/jn.00129.2003
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Entrainment to Temperature, But Not Light, in the Isolated Suprachiasmatic Nucleus

Abstract: . The suprachiasmatic nucleus (SCN) is the master pacemaker that drives circadian rhythms in mammalian physiology and behavior. The abilities to synchronize to daily cycles in the environment and to keep accurate time over a range of physiologic temperatures are two fundamental properties of circadian pacemakers. Recordings from a bioluminescent reporter (Per1-luc) of Period1 gene activity in rats showed that the cultured SCN entrained to daily, 1.5°C cycles of temperature, but did not synchronize to daily lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 72 publications
4
62
1
Order By: Relevance
“…3). The phase shift induced by changing the ambient temperature in our experiments is consistent with a previous study that demonstrated that the SCN entrains to temperature cycles (Herzog and Huckfeldt, 2003).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…3). The phase shift induced by changing the ambient temperature in our experiments is consistent with a previous study that demonstrated that the SCN entrains to temperature cycles (Herzog and Huckfeldt, 2003).…”
supporting
confidence: 92%
“…3). The phase shift induced by changing the ambient temperature in our experiments is consistent with a previous study that demonstrated that the SCN entrains to temperature cycles (Herzog and Huckfeldt, 2003).In summary, our results demonstrate that the periods of mammalian peripheral tissues are temperature compensated over the range of 29 to 37 °C. We find tissuespecific differences in the Q 10 and in temperature-induced shifts of circadian phase.…”
supporting
confidence: 92%
“…Nonetheless, it should be noted that the resilience of the SCN to temperature changes is somewhat controversial. Herzog and Huckfeldt (2003) reported that in vitro cultured SCN preparations from rats synchronized readily to 24-h temperature cycles. Ruby (2011) suggested that different explant sizes and culture conditions may account for the somewhat incoherent observations made in studies with SCN tissue.…”
Section: Body Temperature Rhythms As Zeitgebers For Peripheral Circadmentioning
confidence: 99%
“…Yet, the cellular clocks tick at approximately the same rate at different ambient temperatures and, in mammals, even at a slightly higher pace when temperature is decreasing (Izumo et al 2003;Tsuchiya et al 2003;Dibner et al 2009). In spite of the resilience of the circadian period length over physiologically occurring temperature ranges, temperature oscillations have been demonstrated to act as strong Zeitgebers in multiple species from unicellular organisms to mammals (Zimmerman et al 1968;Francis and Sargent 1979;Underwood and Calaban 1987;Brown et al 2002;Herzog and Huckfeldt 2003;Boothroyd et al 2007).…”
mentioning
confidence: 99%
“…One obvious change associated with general anesthesia is transient hypothermia. Changes in temperature can phaseshift circadian neuronal rhythms of suprachiasmatic nuclei maintained in vitro (Herzog and Huckfeldt, 2003;Ruby et al, 1999), raising the possibility that anesthesia-induced hypothermia plays an active role in the observed phaseshifts. Notably, hypothermia reached the lowest (absolute) values after propofol perfusion at the sleep/wake transition (ie at circadian time 10), the same time as propofol treatment induced subsequent phase-advances (Figures 3 and 5).…”
Section: Chronobiotic Effects Of Propofol Anesthesiamentioning
confidence: 99%